Sub-pingo water lenses, Tuktoyaktuk Peninsula, Northwest Territories - Mackay, J. Ross (Canadian Journal of Earth Sciences, 1978)
In 1976 and 1977 three growing pingos were drilled for the purpose of measuring sub-pingo water pressures beneath aggrading permafrost. All holes drilled through permafrost in the pingos and adjacent lake flats produced artesian flow. The flow from the pingos was clear and as the gushers rose to a maximum height of 3 m above ground level, large sub-pingo water lenses under pressure seemed evident. The existence of the lenses was confirmed by sounding their depths once permafrost was penetrated.One pingo had a 2.2 m deep water lens beneath the top. Pressure transducers, installed in the sub-pingo water lenses or in the unfrozen sands beneath, all indicated pressure heads above the tops of the pingos. Precise levelling of bench marks showed that the top of one pingo subsided 60 cm from drill hole water loss. Calculations for one pingo show that the water lens has likely been present since the birth of the pingo. Recharge from a distant source cannot account for the high pressures because the hydrostatic heads are above the pingo tops and as the pingo tops are usually the highest features in Tuktoyaktuk Peninsula, there can be no available higher source area; even if there were distant sources, the countless intervening lakes would quickly release any artesian pressures; and numerous pingos have grown up in drained lakes which are either too small or too young to have through-going taliks beneath them. Therefore, the observed water lenses and high sub-pingo pore water pressures cannot be attributed to recharge but provide strong field evidence for pressure generated by pore water expulsion.